Randomized Vehicle-Controlled Study of Short Drug Incubation Aminolevulinic Acid Photodynamic Therapy for Actinic Keratoses of the Face or Scalp. Issue 3 (March 2016) - Pariser, David M.; Houlihan, Anna; Ferdon, Mary Beth; Berg, James E.
Abstract : BACKGROUND: Aminolevulinic acid photodynamic therapy (ALA-PDT) can be effective and well tolerated when applied over a broad area and for short drug incubation times. OBJECTIVE: To evaluate the effect of short-incubation time and application method on the safety and efficacy of ALA-PDT versus vehicle (VEH-PDT) in the treatment of actinic keratoses (AKs) of the face or scalp. METHODS: Aminolevulinic acid or VEH was applied to face or scalp as a broad area application for 1, 2, or 3 hours or as a spot application for 2 hours before blue light activation. An identical treatment was repeated at Week 8 if any AK lesions remained. RESULTS: Median AK clearance rate for ALA-treated subjects ranged from 68% to 79% at Week 12, compared with 7% of the VEH-treated group ( p < .0001). Complete clearance rate for ALA-treated subjects ranged from 17% (8/46) to 30% (14/47) at Week 12, compared with 2% (1/46) of the VEH-treated group ( p = .0041). The safety profile seen in this study is consistent with previously reported side effects of the therapy. CONCLUSION: Short-incubation ALA-PDT was found to be superior to VEH-PDT for AK lesion clearance. A second treatment improves efficacy.